Keeping the faith in exile: Kuwait-Coptic Orthodox diasporic spirituality - Crace, Benjamin Daniel (Theology and mission in world christianity, 2024)
"Few churches today can trace their lineage as far back as the Copts. Their ancient traditions and rituals go back as far as the very beginnings of Christianity. For centuries, they have withstood many trials and martyrdoms. But in the twentieth century, many Copts left their homeland and scattered all over the Earth, seeking prosperity and security. Many went to the West, but many others went to the heart of the Islamic world: the Arabian Gulf. They took their faith with them into this new and challenging environment. In this context, hybrid forms of spirituality emerged, anchored in the ancient practices but sharpened by contact with globalisation. This migrant spirituality characterises their stories and touches the heart of what it means to be a Christian sojourner today"--